KAJIAN YURIDIS PERJANJIAN PENGELOLAAN KOLAM RENANG LANGEN TIRTA KEMBAR ANTARA PEMERINTAH KABUPATEN BANYUMAS DENGAN PT GRAHA CIPTA GUNA - Pangestika Rizki Utami (Jurnal Idea Hukum, 2015)
Management Agreement Langen Tirta Kembar swimming pool is a form the government of Banyumas in order to improve the optimization of the utilization of the asset management region. Management agreement has been agreed on 25 July 1988, during the management period of 30 (thirty) years. But since 25 June 2007 Langen Tirta Kembar Swimmingpool closed due to poor water supply problems. This research is to analyze the construction for management agreement and also to analyze the problem solving of Management Agreement of Langen Tirta Kembar Swimmingpool between the Government of Banyumas Regency and PT Graha Cipta Guna. This research is normative legal with conceptual and analytical approach. It is descriptive specification. This is from Center for Scientific Information Faculty of Law Jenderal Soedirman University, Library of Jenderal Soedirman University, The Government of Banyumas regency, PT Graha Cipta Guna, and The law court of Purwokerto. This legal materials sources by primary legal materials, secondary, and tertiary. The method collection of legal materials by library study. Presentment method of legal materials by descriptive-narrative. Analysis of legal materials with descriptive qualitative method.Keywords : Agreement, Management of asset region